First information about soil nematodes in the meadow ecosystems of Chernіhiv Region (Ukraine) - Шевченко, В. Л.; Жиліна, Т. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
Soil nematode fauna of the natural meadow ecosystems was studied for the first time in two administrative districts in the northeast and northwest of Chernihiv Region. A total of 62 species from 30 families and 7 orders was registered. The orders Tylenchida, Rhabditida and Dorylaimida were the most species-rich and numerous in individual numbers. Average nematode number in the soil samples was 756 specimens/100 g. Eleven species occurred in more than 50% of the samples. Of these, Aphelenchus avenae was the most widespread. There were 12 phytohelminth species recorded.